Androgen controlled secondary sexual characters in the male African clawed frog, Xenopus laevis, as potential biomarkers for endocrine disruptor contaminants (with special reference to fungicides) in aquatic systems - Archer, Edward (Stellenbosch : Stellenbosch University, 2014)
Thesis (MSc)--Stellenbosch University, 2014.